Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmed.2021.659793
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Critically Ill COVID-19 Patients With and Without Extracorporeal Membrane Oxygenation Support in Wuhan, China

Abstract: Background: Extracorporeal membrane oxygenation (ECMO) might benefit critically ill COVID-19 patients. But the considerations besides indications guiding ECMO initiation under extreme pressure during the COVID-19 epidemic was not clear. We aimed to analyze the clinical characteristics and in-hospital mortality of severe critically ill COVID-19 patients supported with ECMO and without ECMO, exploring potential parameters for guiding the initiation during the COVID-19 epidemic.Methods: Observational cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Of 2888 studies identified ( figure ), we selected 123 for full-text review. We included 42 observational cohort studies 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 involving 17 449 patients ( table 1 ), predominantly from North America or Europe. We did not identify any randomised controlled trials that met our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 2888 studies identified ( figure ), we selected 123 for full-text review. We included 42 observational cohort studies 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 involving 17 449 patients ( table 1 ), predominantly from North America or Europe. We did not identify any randomised controlled trials that met our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“… 35 , 36 , 37 , 38 , 39 Studies were judged to be at some risk of bias for confounding adjustment and for statistical analysis and reporting if they did not account for clinically important confounders using either logistic regression or Cox proportional hazards models. 15 , 39 , 44 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 Studies reporting adjusted analyses were judged to be at some risk of bias for statistical analysis 35 , 36 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 if they did not adhere to methodological standards set by the PROGRESS guidelines, 19 , 20 , 21 , 22 in particular with regards to a priori selection of clinically important confounders and consideration of an appropriate sample size to minimise potential overfitting. 28 , 76 The composition and methodological quality of individual prediction models for each study and funnel plots used to evaluate for publication bias among variables that were assessed in at least ten studies are included in the appendix (p 36–41 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , Additional file 1 : Table S4) [ 3 , 5 , 16 65 ]. All studies were retrospective and observational in nature; 22 studies were conducted by studies centres from Europe [ 5 , 17 , 19 , 23 , 27 , 29 , 31 – 34 , 36 , 39 , 42 , 43 , 45 , 46 , 50 , 55 , 56 , 60 , 63 , 65 ], 17 from North America [ 16 , 18 , 20 22 , 24 , 25 , 37 , 40 , 47 , 48 , 52 54 , 57 , 58 , 61 ], 6 from the Asia–Pacific [ 26 , 28 , 35 , 38 , 41 , 44 ], 2 from South-West Asia and Africa,[ 51 , 62 ] 2 from Latin America [ 30 , 64 ], and 3 were studies conducted by centres from multiple ELSO regions [ 3 , 49 , 59 ], of which 2 were based on registry data [ 3 , 49 ]. The pooled age was 52.5 years (95% CI 50.7 to 54.3), and the majority of patients were male (75.0%, 95% CI 72.4% to 77.4%) and obese (BMI: 31.0, 95% CI 30.2 to 31.8).…”
Section: Resultsmentioning
confidence: 99%
“…In the early stage of the pandemic in Wuhan, some hospitals used the supportive care combined with antivirals and glucocorticoids, resulting in high mortality and low cure rate [19] , [20] , [21] , [22] , [23] . After TCM participation, the mortality rate was significantly reduced.…”
Section: Introductionmentioning
confidence: 99%